Faktor-Faktor yang Mempengaruhi Optimalisasi Aset Negara: Inventarisasi Aset, Perencanaan Kebutuhan Aset, dan Pengawasan dan Pengendalian Aset - Widayat, Widi; Kuntadi, Cris; Karunia, R. Luki (Jurnal Manajemen, Akuntansi dan Logistik (JUMATI), 2024)
State asset optimization needs to be strengthened to create added value for society, so that it can produce financial benefits in the form of Non-Tax State Income and non-financial benefits. This article reviews the factors that influence the Optimization of State Assets, namely Asset Inventory, Asset Needs Planning and Asset Supervision and Control. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further research. Based on qualitative methods through library research by studying theories and relationships or influences between variables from books and journals both offline in the library and online. The results of this article's literature review are: 1) Asset Inventory affects State Asset Optimization; 2) Asset Requirements Planning affects the Optimization of State Assets; and 3) Asset Supervision and Control affects the Optimization of State Assets. Keywords: State Asset Optimization, Asset Inventory, Asset Requirement Planning, and Asset Supervision and Control